Comparação dos resultados intraoperatórios e pós-operatórios imediatos em pacientes submetidos à prostatectomia radical laparoscópica pura e assistida por robô - Rodrigo Lolli Almeida Salles (2022)
BACKGROUND: Radical prostate surgery is one of the treatment modalities for prostate cancer. There has been an evolution of surgical techniques with a tendency towards those that are minimally invasive, and we currently have laparoscopy and the aid of a robotic platform. Knowing the results after radical prostatectomy using different minimally invasive techniques helps us to better inform patients with prostate cancer who need surgical treatment about the risks and benefits of these treatment modalities. OBJECTIVES: To compare the immediate operative results of patients with localized prostate cancer who underwent pure laparoscopic (PRL) and robot-assisted prostatectomy (PRAR) in two tertiary referral hospitals in the city of Belo Horizonte, operated by a single surgeon. METHODS: A retrospective analysis of data from patients with localized prostate cancer who underwent radical prostatovesiculectomy using minimally invasive approaches was performed. Patients from all risk groups for extraprostatic disease according to the D'Amico risk classification1 were included. The procedures were performed by a single surgeon with a high level of experience in laparoscopic and robotic surgery. All preoperative and perioperative data were compiled in a database built with the REDCap (Research Electronic Data Capture) platform under license from Vanderbilt University. Data such as estimated bleeding, length of hospital stay and postoperative complications were evaluated, as well as the characteristics of the surgical specimen evaluated in the pathology department. Martin's 2 criteria were used for adequate data acquisition of complications, and these were classified using the method proposed by Clavien. 3 RESULTS: in total, data from 378 patients were analyzed. Patients undergoing PRL had a longer hospital stay, but showed a slight benefit in estimated bleeding. There was no difference in operative time, conversion rate to conventional surgery, and rate of positive surgical margins. The number of lymph nodes removed in extended lymphadenectomy was higher when using the robotic platform. CONCLUSIONS: the two minimally invasive techniques are safe and reproducible, with results that, for the most part, are similar.